Dietary Supplementation With Acer truncatum Oil Promotes Remyelination in a Mouse Model of Multiple Sclerosis - Yuhuan Xue; Xiaoyan Zhu; Wenyong Yan; Zhihan Zhang; Enhui Cui; Yongji Wu; Cixia Li; Jiarong Pan; Qijiang Yan; Xuejun Chai; Shanting Zhao (Frontiers in Neuroscience, 2022)
BackgroundMultiple sclerosis is a chronic demyelinating disease of uncertain etiology. Traditional treatment methods produce more adverse effects. Epidemiological and clinical treatment findings showed that unknown environmental factors contribute to the etiology of MS and that diet is a commonly assumed factor. Despite the huge interest in diet expressed by people with MS and the potential role diet plays in MS, very little data is available on the role of diet in MS pathogenesis and MS course, in particular, studies on fats and MS. The oil of Acer truncatum is potential as a resource to be exploited in the treatment of some neurodegenerative diseases.ObjectiveHere, we investigated the underlying influences of Acer truncatum oil on the stimulation of remyelination in a cuprizone mouse model of demyelination.MethodsCuprizone (0.2% in chow) was used to establish a mouse model of demyelination. Acer truncatum oil was administrated to mice during remyelination. Following techniques were used: behavioral test, histochemistry, fluorescent immunohistochemistry, transmission electron microscope.ResultsMice exposed to cuprizone for 6 weeks showed schizophrenia-like behavioral changes, the increased exploration of the center in the open field test (OFT), increased entries into the open arms of the elevated plus-maze, as well as demyelination in the corpus callosum. After cuprizone withdrawal, the diet therapy was initiated with supplementation of Acer truncatum oil for 2 weeks. As expected, myelin repair was greatly enhanced in the demyelinated regions with increased mature oligodendrocytes (CC1) and myelin basic protein (MBP). More importantly, the supplementation with Acer truncatum oil in the diet reduced the schizophrenia-like behavior in the open field test (OFT) and the elevated plus-maze compared to the cuprizone recovery group. The results revealed that the diet supplementation with Acer truncatum oil improved behavioral abnormalities, oligodendrocyte maturation, and remyelination in the cuprizone model during recovery.ConclusionDiet supplementation with Acer truncatum oil attenuates demyelination induced by cuprizone, indicating that Acer truncatum oil is a novel therapeutic diet in demyelinating diseases.